2021
DOI: 10.1016/j.dib.2021.106728
|View full text |Cite
|
Sign up to set email alerts
|

2019 Ambon aftershocks catalogue data compiled using local and regional seismic networks

Abstract: This article presents earthquake catalogs of the 2019 Ambon aftershocks compiled from regional the Agency for Meteorology, Climatology, and Geophysics of Indonesia (BMKG) and local seismic networks deployed in [1] . The final earthquake catalogs are comprised of 1009 and 1764 aftershocks compiled from regional [2] and local network [1] , respectively, which span the period of October 18th to December 15th, 2019. The range of their spatial reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This earthquake is caused by the deformation of rocks with active fault movement mechanisms, this is due to a complicated tectonic order [7], [8]. This tectonic order is directly related to the activity of banda volcanoes, and the topographic form of Maluku Province [9]. The National Disaster Management Agency (2019) reported that the quake caused damage to buildings and public facilities, more than 6000 buildings were damaged, 41 people died, and 1,578 others were injured.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This earthquake is caused by the deformation of rocks with active fault movement mechanisms, this is due to a complicated tectonic order [7], [8]. This tectonic order is directly related to the activity of banda volcanoes, and the topographic form of Maluku Province [9]. The National Disaster Management Agency (2019) reported that the quake caused damage to buildings and public facilities, more than 6000 buildings were damaged, 41 people died, and 1,578 others were injured.…”
mentioning
confidence: 99%
“…The National Disaster Management Agency (2019) reported that the quake caused damage to buildings and public facilities, more than 6000 buildings were damaged, 41 people died, and 1,578 others were injured. About 150,000 people were evacuated to safer ground, due to frequent aftershocks and fears of a tsunami from the quake [6], [9] Based on the geographical and geological conditions of Ambon City is an area prone to earthquake disasters because it is close to the kolisi zone in the banda arc [10], [7] Galih & Handayani in 2007 has previously conducted research on mapping the pattern of earthquakes in Indonesia with fractal methods, he argues that Maluku is the highest potential area for earthquake disasters [11]. With growing obtained from BAPPEKOT Ambon have been carried out radiometric correction and geometric correction process and rgb band composite has been done.…”
mentioning
confidence: 99%